问题 解答题
(1)
3
4
+
3
4
÷3+
9
25
(2)
1
3
÷
1
2
-
5
4
×
2
5
(3)
4
9
÷(
5
9
-
5
18
(4)
1
4
÷(
2
3
-
3
2
×
1
3
)            
(5)
5
8
×
3
4
+
1
4
×
5
8
(6)(
3
4
+
2
5
)×40.
答案

(1)

3
4
+
3
4
÷3+
9
25

=

3
4
+
1
4
+
9
25

=1+

9
25

=1

9
25

(2))

1
3
÷
1
2
-
5
4
×
2
5

=

2
3
-
1
2

=

1
6

(3)

4
9
÷(
5
9
-
5
18
),

=

4
9
÷
5
18

=

8
5

(4)

1
4
÷(
2
3
-
3
2
×
1
3
),

=

1
4
÷(
2
3
-
1
2
),

=

1
4
÷
1
6

=

3
2

(5)

5
8
×
3
4
+
1
4
×
5
8

=

5
8
×(
3
4
+
1
4
),

=

5
8
×1,

=

5
8

(6))(

3
4
+
2
5
)×40,

=

3
4
×40+
2
5
×40,

=30+16,

=46.

选择题
判断题